Practical considerations for assessing pulmonary gas exchange and ventilation during flume swimming using the MetaSwim metabolic cart - Lomax, M.; Mayger, B.; Saynor, Z. L.; Vine, C.; Massey, H. C. (The Journal of Strength and Conditioning Research, 2019)
The MetaSwim (MS) metabolic cart can assess pulmonary gas exchange and ventilation in aquatic environments. The aims of this study were: (a) to determine the agreement between minute ventilation (VE), pulmonary oxygen uptake (VO2), and carbon dioxide output (VCO2) using the MS and Douglas bag (DB) methods during flume swimming; and (b) to assess the repeatability of these and other MS-derived parameters. Sixteen trained swimmers completed a combined incremental and supramaximal verification cardiopulmonary swimming test to determine maximal VO2, 2 progressive intensity swimming tests during which MS and DB measurements were made (agreement protocol), and 3-4 constant-velocity submaximal swimming tests during which only the MS was used (repeatability protocol). Agreement was determined using limits of agreement (LoA), bias, random error, and 95% confidence intervals with systematic bias assessed using paired samples t-tests. Within-trial and between-trial repeatability were determined using the coefficient of variation (CV) and the repeatability coefficient (CR). Where data were heteroscedastic, LoA and CR were log-transformed, antilogged, and displayed as ratios. MetaSwim underestimated peak VO2 and VCO2 (=0.39 L/min) and VE (9.08 L/min), whereas submaximal values varied between 2 and 5% for CV and ±1.09-1.22 for ratio CR. The test-retest CV during constant-velocity swimming for VE, tidal volume, breathing frequency, VO2, VCO2, and end-tidal pressures of O2 and CO2 was <9% (ratio CR of ±1.09-1.34). Thus, the MS and DB cannot be used interchangeably. Whether the MS is suitable for evaluating ventilatory and pulmonary responses in swimming will depend on the size of effect required.